Efavirenz Binding to HIV-1 Reverse Transcriptase Monomers and Dimers - Braz, Valerie A. (2010)
Efavirenz (EFV) is a nonnucleoside reverse transcriptase inhibitor (NNRTI) of HIV-1 reverse transcriptase (RT) used for the treatment of AIDS. RT is a heterodimer composed of p66 and p51 subunits; p51 is produced from p66 by C-terminal truncation by HIV protease. The monomers can form p66/p66 and p51/p51 homodimers as well as p66/p51 heterodimer. Dimerization and efavirenz binding are coupled processes. In the crystal structure of the p66/p51—EFV complex, the drug is bound to the p66 subunit. The binding of efavirenz to wild-type and dimerization-defective RT proteins was studied by equilibrium dialysis, tryptophan fluorescence and native gel electrophoresis. A 1:1 binding stoichiometry was determined for both monomers and homodimers. Equilibrium dissociation constants are ~2.5 μM for both p66— and p51—EFV complexes, 250 nM for p66/p66—EFV complex, and 7 nM for p51/p51—EFV complex. An equilibrium dissociation constant of 92 nM for p66/p51—EFV complex was calculated from the thermodynamic linkage between dimerization and inhibitor binding. Binding and unbinding kinetics monitored by fluorescence were slow. Progress curve analyses revealed a one-step, direct binding mechanism with association rate constants k(1) ~13.5 M(–1) s(–1) for monomers and heterodimer and dissociation rate constants k(–1) ~1 × 10(–4) s(–1) for monomers. A conformational selection mechanism is proposed to account for the slow association rate. These results show that efavirenz is a slow, tight-binding inhibitor capable of binding all forms of RT and suggest that the NNRTI binding site in monomers and dimers is similar.